Protective effect of cocoa extract on ethanol induced liver Injury in Sprague-dawley rats - Rosmawati Mat Shair; Mohamad Yusof Maskat; Mohamad Khan Ayob; Rosmin Kasran (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cocoa is a rich source of dietary polyphenol, highly potential antioxidant against free radicals. This study was designed to identify the effect of cocoa polyphenol extract in protecting from ethanol-induced liver injury in rats. Fifty male Sprague-dawley rats were divided into five groups fed with or without ethanol (4 g/kg/d), cocoa extract (300 mg/kg/d) and silymarin (200 mg/kg/d) continuously for 3 weeks using an enteral feeding protocol. All treatments were given orally every day for three weeks and continuously supply food and water ad libitum. Results showed that cocoa extract (CE) from unfermented cocoa beans had a total polyphenol content of 335.70±27.51 mg GAE/g and 38.10±4.52 mg CaE/g. Meanwhile, analysis normal phase-high performance liquid chromatography shows CE contains 59.47±9.44 mg/g and 14.69±1.63 mg/g of epicathechin and catechin, respectively, which is three fold higher compared to commercial cocoa powder. It also contains 59.69±2.15 mg/g theobromine which also three fold higher compared to caffeine 19.87±1.37 mg/g. In vitro study showed cocoa extract contains high antioxidant activities by 91.9±1.00 % against superoxide scavenging system (O2-) and 97.7±0.15% against α-α-diphenyl-β-picrylhydrazyl radical (DPPH) systems. In vivo study showed increasing level in both liver function enzymes, aspartase aminotransferase (AST) and alanine aminotransferase (ALT) in ethanol intoxication by 116.80±5.23 mmol/L and 56.37±2.71 mmol/L, respectively. Ethanol intoxication was blocked by cocoa extract nearly 89.95±1.18 mmol/L and 46.75±0.74 mmol/L, respectively, and it was comparable with SDT group for both enzymes AST and ALT by 112.19±6.02 mmol/L and 42.49±0.62 mmol/L, respectively. Furthermore, ethanol groups showed significantly lower (p<0.05) of glutathione level by 0.29 ±0.03 μmol/g, however cocoa extract with antioxidant defense system either direct or indirectly protect liver injury by increasing glutathione level at 0.53±0.02 μmol/g. As a result, cocoa extract shows its potential as antioxidant agents to protect ethanol-induced liver injury.